1998
DOI: 10.1016/s0736-5748(98)00030-6
|View full text |Cite
|
Sign up to set email alerts
|

Anterior pituitary response to stress : time‐related changes and adaptation

Abstract: A wide array of physical and psychological stressors alter the secretion of anterior pituitary hormones. However, both the qualitative and the quantitative features of the stressors as well as its duration markedly influence the final endocrine response. In addition, among all anterior pituitary hormones, only ACTH and prolactin levels appear to reflect the intensity of the stress experienced by the animals. Although physical stressors show a somewhat specific neuroendocrine profile, the response of the pituit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 208 publications
7
85
0
5
Order By: Relevance
“…The lower dose of nalbuphine was significantly correlated with "Sick". These subjective ratings are consistent with the classification of PRL as a stress-reactive hormone (Marti and Armario, 1998). In our previous studies, no change from baseline in subjective effects was observed after vehicle administration alone (Mendelson et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…The lower dose of nalbuphine was significantly correlated with "Sick". These subjective ratings are consistent with the classification of PRL as a stress-reactive hormone (Marti and Armario, 1998). In our previous studies, no change from baseline in subjective effects was observed after vehicle administration alone (Mendelson et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Because stress-induced increases in plasma glucose are an index of the activation of the adrenal medulla and particularly of plasma adrenaline (Martí and Armario, 1998), the present finding argues against an effect of juvenile stress on the activation of the sympathetic-medulloadrenal axis. Despite this severity, IMO by itself had no long-term (7 days post-stress) anxiogenic effects in the EPM.…”
Section: Accepted M Manuscriptmentioning
confidence: 49%
“…Under certain conditions, the impact of repeated challenges is reduced through adaptive mechanisms, generally termed habituation (Christoffersen, 1997), that act to minimize further physical and psychological insult. In general, habituation to glucocorticoid and catecholamine release, some of the most widely studied stress responses, often develop following the relatively predictable exposures of experimental animals to the same (homotypic) stressor (McCarty et al, 1992;Marti and Armario, 1998). Importantly, these responses are either normal or facilitated in habituated animals exposed to a different (heterotypic), not previously experienced stressor (Marti and Armario, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In general, habituation to glucocorticoid and catecholamine release, some of the most widely studied stress responses, often develop following the relatively predictable exposures of experimental animals to the same (homotypic) stressor (McCarty et al, 1992;Marti and Armario, 1998). Importantly, these responses are either normal or facilitated in habituated animals exposed to a different (heterotypic), not previously experienced stressor (Marti and Armario, 1998). These findings have led to the suggestion that habituation occurs in the central limb of stress-responsive circuits (Akana and Dallman, 1997), thus allowing the hypothalamo-pituitary-adrenocortical (HPA) axis to respond normally, or even become sensitized, to new challenges.…”
Section: Introductionmentioning
confidence: 99%